1992
DOI: 10.1063/1.351876
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature epitaxial growth of Ag on low-index Si surfaces by a partially ionized beam

Abstract: Carbon segregation to the lowindex surfaces of an Fe-10 at.% Si single crystal The room temperature growth of 1000-1500 b; Ag films on HF-dipped Si substrates is studied as a function of self-ion (Ag+ ) energy during deposition. In all cases the tilms contained a mixture of epitaxial grains and randomly oriented ( 111) grains. The orientations observed were Ag(lll)/Si(lll) with both type A (Ag(llO)//Si(llO)) and type B (Ag(llO)//Si(ll4)) twins; Ag( 1 lO)/Si( 110) with Ag(OOl)//Si(OOl);and Ag( lOO)/Si( 100) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Therefore, it was difficult to grow a Ag film epitaxially on the Si surface. However, according to the domain matching epitaxy concept, Ag can grow epitaxially on the Si surface due to the 3 Si -to-4 Ag lattice matching. , We also found that the Ag–Si interfacial structure was constructed by 3 Si -to-4 Ag matching on the atomic scale (the right side of Figure a), indicating the absence of recombination processes caused by defects, dislocations, or Si dangling bonds. The obtained results also demonstrated the presence of Pb atoms in the produced crystallites (Figure b,c and Figure S6), and relative contents of Ag and Pb elements were 97.54 and 2.46 wt %, respectively (Figure S7).…”
Section: Results and Discussionmentioning
confidence: 65%
“…Therefore, it was difficult to grow a Ag film epitaxially on the Si surface. However, according to the domain matching epitaxy concept, Ag can grow epitaxially on the Si surface due to the 3 Si -to-4 Ag lattice matching. , We also found that the Ag–Si interfacial structure was constructed by 3 Si -to-4 Ag matching on the atomic scale (the right side of Figure a), indicating the absence of recombination processes caused by defects, dislocations, or Si dangling bonds. The obtained results also demonstrated the presence of Pb atoms in the produced crystallites (Figure b,c and Figure S6), and relative contents of Ag and Pb elements were 97.54 and 2.46 wt %, respectively (Figure S7).…”
Section: Results and Discussionmentioning
confidence: 65%
“…The weak spots in the RHEED patterns are indeed very weak and can be associated with a very small number of Ag(100) islands as observed in ref. [36,38] for Ag growth on Si(111) surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…7(d) we notice that the intensities of diffraction spots from each twin are comparable, indicating their comparable probability of existence in the Ag nanoislands. Almost comparable number of A-type 13 and B-type grain growth was also observed for Ag growth on Si(111) surfaces [36,38]. The epitaxial orientation of the Ag islands with the A-type structure is schematically shown in Fig.…”
mentioning
confidence: 96%
“…Therefore, it was difficult to grow an Ag film epitaxially on the Si surface. However, according to the domain matching epitaxy concept [32][33][34] , Ag can grow epitaxially on the Si surface due to the 3Si-to-4Ag lattice matching 31,[34][35][36][37][38] . We also found that the Ag-Si interfacial structure was constructed by the 3Sito-4Ag matching on the atomic scale (the right side of Fig.…”
Section: Mechanism Of Ag Crystallite Formationmentioning
confidence: 99%